A scoping review of best practices in home enteral tube feeding. (4th August 2022) - Byrnes, Cliona; Mockler, David; Lyons, Linda; Loane, Dorothy; Russell, Edel; Bennett, Annemarie E.
Abstract: Aims: To review the experiences of healthcare professionals (HCPs) and service users on the provision and receipt of home enteral nutrition (HEN) in primary care settings, respectively. Backgrounds: HEN supports the nutritional needs of service users in primary care settings who are unable to meet their nutritional requirements through oral intake alone. While HEN supports service users to remain in their home, the provision of HEN services can be variable. The prevalence of HEN is increasing as health systems shift delivery of care from acute to primary care settings, and therefore the evolving needs of HCPs and service users in relation to HEN deserve exploration. Methods: Quantitative and qualitative studies were included if they described (1) practices that support best outcomes in adults on HEN and residing in their own homes and/or (2) service user and HCP experiences of HEN. Studies on the economics of HEN were included. Databases searched included MEDLINE/PubMed, EMBASE, Web of Science, and CINAHL. Publications up to March 2021 were included. A descriptive analytical approach was used to summarise the findings. Findings: Key themes included the importance of initial education to enable service users to adapt to HEN and the need for support from knowledgeable HCPs. Access to support from HCPs in primary care was limited, and some HCPs felt their knowledge of HEN was inadequate. Service users highlighted the significant impact of HEN on daily living and emphasised the need for support from a HEN team. HEN services were also associated with reduced hospital admissions, lengths of stay in hospital, and costs of hospitalisation. Conclusions: A specialist HEN service can manage enteral nutrition-related complications, reduce unnecessary hospital admissions, and improve quality of care and patient satisfaction. Further education of HCPs is needed on the provision of HEN.